Synoptic Analysis of Winter Frosts in Sistan Region (Case Study: The Frost January 2008) - Mahmood Khosravi; Nematollah Safarzaie; Mohsen Armesh (نشریه جغرافیا و برنامه‌ریزی, 2015)
Frost is one of the natural disasters that is usually are associated with financial losses and even mortality. The atmospheric circulation systems have a main role in the occurrence, severity and spatial distribution of frost especially in temperate regions. The purpose of this research is the detection and investigation of synoptic conditions simultaneous with occurrence of winter frosts in Sistan region. The method used in this analysis approach is peripheral circulation. For these purposes, two databases (surface and atmospheric) were required. For surface data, climate data from synoptic weather stations of Zabol and Zahak were used as a representative of the regional climate. The longest and most severe frost was selected during the last decade (2010-2000). Second database of sea level data and maps of 850 and 500 Hp levels was prepared from the National Center for Environmental Prediction (NCEP) and National Center for Atmospheric Research (NCAR). Spatial coverage of weather data is between 30 until 90 degrees east longitudes and 10 until 50 degrees north latitude. For representing the weather stream lines maps, Grads software was used. The results showed that cyclonic activity on the Balkhash Lake prepared the situation for downfall of cold air of high latitude and western flow of trough to region and caused frost in the Sistan region. Transferred axis of trough at the eastern regions and the above conditions caused more frost persistence. The most severe frost in Sistan region tll, place in the western part of trough and the flux of northern cold air. The factor that has created these conditions is the pressure gradient between the southern and northern regions of Sistan, especially South East of Sistan low-pressure system which led to the establishment of west part of trough to the region.